Production and exportation of eggs of laying hens in Brazil (Research, Society and Development, 2022)
The objective of the study was to evaluate the evolution of the production and export of eggs of commercial laying hens in Brazil, considering the period from 2007 to 2021. Methodological procedures were used that included, besides literature and documentary research, collection and analysis of information obtained from government agencies and press responsible for the sector. In addition, in 2020, Brazil was the 5th largest producer of commercial eggs. In 2021, the southeast region was the main Brazilian egg producer and Brazilian egg consumption was 257 eggs per capita which are lower than other countries. For example, Mexican and American consumptions of eggs per capita were respectively, 368 (2020) and 289 (2019). Through the years, 2007-2021 there was an increase of 49.03% in the per capita consumption of eggs by Brazilians. In the last year, Brazilian eggs exported were inexpressive with 0.46% of the total produced: 69.7% eggs in natura and 30.3% industrialized eggs. For the coming years, there are expectations of improvements with the opening of new markets. Brazil has shown continuous growth in both egg production and in per capita consumption of eggs. There is a need for investment in new technologies, as well as improvement to health and food safety norms. In addition, the Brazilian agency needs to be more effective in disseminating egg nutritional values. The action of the Brazilian egg agency must be more active to explore the internal and external market of industrialized eggs.